Different Continuous Cropping Spans Significantly Affect Microbial Community Membership and Structure in a Vanilla-Grown Soil as Revealed by Deep Pyrosequencing - Xiong, Wu; Zhao, Qingyun; Zhao, Jun; Xun, Weibing; Li, Rong; Zhang, Ruifu; Wu, Huasong; Shen, Qirong (Microbial ecology, 2015)
In the present study, soil bacterial and fungal communities across vanilla continuous cropping time-series fields were assessed through deep pyrosequencing of 16S ribosomal RNA (rRNA) genes and internal transcribed spacer (ITS) regions. The results demonstrated that the long-term monoculture of vanilla significantly altered soil microbial communities. Soil fungal diversity index increased with consecutive cropping years, whereas soil bacterial diversity was relatively stable. Bray-Curtis dissimilarity cluster and UniFrac-weighted principal coordinate analysis (PCoA) revealed that monoculture time was the major determinant for fungal community structure, but not for bacterial community structure. The relative abundances (RAs) of the Firmicutes, Actinobacteria, Bacteroidetes, and Basidiomycota phyla were depleted along the years of vanilla monoculture. Pearson correlations at the phyla level demonstrated that Actinobacteria, Armatimonadetes, Bacteroidetes, Verrucomicrobia, and Firmicutes had significant negative correlations with vanilla disease index (DI), while no significant correlation for fungal phyla was observed. In addition, the amount of the pathogen Fusarium oxysporum accumulated with increasing years and was significantly positively correlated with vanilla DI. By contrast, the abundance of beneficial bacteria, including Bradyrhizobium and Bacillus, significantly decreased over time. In sum, soil weakness and vanilla stem wilt disease after long-term continuous cropping can be attributed to the alteration of the soil microbial community membership and structure, i.e., the reduction of the beneficial microbes and the accumulation of the fungal pathogen.